Educational strategies for human resources in home health care: 8 years' experience from Brazil - Leonardo Cancado Monteiro Savassi; Mariana Borges Dias; Antonio Fernando Boing; Marta Verdi; Alysson Feliciano Lemos (Pan American Health Organization, 2020)
Objective. To analyze characteristics, enrollments and completion rates of healthcare professionals enrolled in Self-Instructional Online Courses of the Home Health Care Multicentre Qualification Program, developed by the Ministry of Health and the Universidade Aberta do SUS (UNASUS), and its relationship with Home Health Care Teams implementation. Methods. Data were extracted from the Self-Instructional Online Courses' UNASUS enrollment platform database (2012-2018), cross-referenced with the Health Facilities' National Database and compared to Home Care General Coordination team's database. Main outcomes were completion rates and number of courses enrollments, analyzed by sex, age, region, location, profession, workplace, health teams and course type. Results. Men applied to courses slightly more than women and completion rates were higher (37.1 vs 30.5, p < 0.001); there was a small decline in completion rates by age groups (from 32.8% in 18-29 yr to 31.1% in 46-50 yr age group, p < 0.001) and a rise in course enrollment number, probably related to progressively "digital native" generations. Self-Instructional Online Courses were attended in all Brazilian states and reached all municipality sizes, with completion rates rising from 29.9% in the North to 37.3 in the South; 30-hour courses were completed by almost twice as many professionals as 45-hour and 60-hour courses, suggesting that modularity may improve completion rates. State distribution and national coverage suggest adequate range and coincidence between enrollment and Home Health Care Teams distribution. Conclusions. Regional aspects influence professional interaction with courses; the feminization of health professions and women's lower completion rates suggest the need for a deeper gender perspective in health facilities and training services. Self- Instructional Online Courses for Home Health Care were an important outreach strategy, with professional's doubts answered more contextually.